Ask Question
16 April, 16:28

Convert the equation from standard form to General form.

(x - 1) 2 + (y + 2) 2 = 16

+2
Answers (1)
  1. 16 April, 18:21
    0
    x² + y² - 2x + 4y - 11 = 0

    Step-by-step explanation:

    Given : (x - 1) ² + (y + 2) ² = 16

    So,

    (x - 1) ² = (x-1) (x-1) = x (x-1) - 1 * (x-1) = x² - x - x + 1 = x² - 2x + 1

    (y + 2) ² = (y+2) (y+2) = y (y+2) + 2 (y+2) = y² + 2y + 2y + 4 = y² + 4y + 4

    ∴ (x - 1) ² + (y + 2) ² = 16

    x² - 2x + 1 + y² + 4y + 4 = 16

    x² + y² - 2x + 4y + 1 + 4 - 16 = 0

    x² + y² - 2x + 4y - 11 = 0

    So, The General form ⇒ x² + y² - 2x + 4y - 11 = 0
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Convert the equation from standard form to General form. (x - 1) 2 + (y + 2) 2 = 16 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers